Non-cooperative polymorphic P systems and parallel communicating ET0L systems: Non-cooperative polymorphic P systems and parallel communicating ET0L systems - Kuczik, Anna; Vaszil, György (Journal of membrane computing, 2025)
We demonstrate that languages of non-cooperative polymorphic P systems with no ingredients (with no special features and no target indicators in the rules) can be generated by nonreturning parallel communicating ET0L systems, and discuss a further topic for research, namely the identification of the subclass of parallel communicating ET0L systems for which the converse of the statement holds, that is, the precise characterization of languages of non-cooperative polymorphic P systems in terms of the parallel communicating Lindenmayer system model.